Perspectives on the physical preparedness of emergency medical care students in South Africa - Mühlbauer, D; Vincent-Lambert, C; Coopoo, Y (Occupational Health Southern Africa, 2025)
Background:Emergency medical care (EMC) and medical rescue environments are physically demanding and potentially hazardous to patients and emergency care providers. Emergency medical care students must be physically prepared to operate effectively and safely in diverse hazardous situations and environments. Currently, little has been published about the unique physical preparedness requirements of EMC students exposed to EMC and medical rescue training.Objectives:To describe the perspectives of academic staff and EMC students, with regards to the physical preparedness of undergraduate EMC students at three higher education institutes (HEIs) in South Africa.Methods:In this descriptive cross-sectional study, a purpose-designed quantitative questionnaire was administered to probe the perspectives of EMC students and academic staff members involved in the teaching of Medical Rescue and Physical Preparedness modules within the undergraduate EMC degree programmes.Results:One hundred and seventeen EMC students and 12 academic staff members participated in the study. Most respondents were male: 77 (65.8%) students and 11 (91.7%) academic staff members. Most students agreed (n = 113, 96.6%) that it is important for EMC students to be physically fit and healthy. There was agreement among students (n = 104, 88.9%) and staff (n = 11, 91.7%) that emergency care and rescue workers should be able to swim. It was agreed that all EMC programmes should assess physical preparedness and use similar assessments.Conclusion:Physical preparedness and the assessment thereof are important components of the EMC degree programme. A validated physical preparedness assessment tool should be developed to address the specific physically strenuous learning outcomes associated with the BHSc EMC programme. This assessment should be standardised at the different HEIs offering the programme, and the assessment should be the same irrespective of student age, sex, and physical attributes.